INOVASI PEMBIAYAAN KPR SYARIAH BERBASIS AKAD ISTISHNA’ DAN IJARAH MUNTAHIYAH BITTAMLIK (IMBT) - Aminarti, Cindy; Salwa, Mazida; Azkiya, Nazilatul; Kamal, Husni (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2025)
This study discusses the implementation of the Ijara Muntahiya Vitamrik (IMBT) contract in fundingfor Sharia apartments in Indonesia. IMBT is an agreement that allows the transfer of propertyownership at the end of the rental period in accordance with the principles of fair luxury and Sharia.The aim of this research is to analyze the supporting and inhibiting factors of implementing IMBT inSharia-KPR product innovation, as well as the actual benefits and challenges in Islamic financialinstitutions. The research method used is explanation by collecting data through literature studies,interviews and observations on the implementation of IMB contracts in several Islamic banks. Theresearch results show that the provisions of Bank of Indonesia and DSN-Mui-Fatwa provide a stronglegal basis for the implementation of the IMB Agreement. However, key challenges include realestate value risks, changes in market prices and the need for strict risk management. In addition,social factors and general understanding of IMBT contracts also influence the implementation of thisproduct. With a regulatory framework that supports support and effective risk management, theimplementation of IMBT will increase the integration of Islamic finance and, according to Sharia,provide an alternative for funding. This study is expected to contribute to the development of Islamicfinancial products and increase public satisfaction in choosing sharia-based real estate solutions.Keywords: IMBT, sharia mortgage, ijarah contract, financial flexibility, sharia financial inclusion